Influence of tillage and weed control practices on growth and yield of wheat. (The Philippine Journal of Crop Science, 2013)
Tillage system in conjunction with weed control strategies can be manipulated as an integrated weed management approach. Influence of different weed control treatments on wheat and its associated weeds was evaluated under conventional, reduced and zero tillage systems. Mature sorghum (Sorghum bicolor L. Moench.) aqueous extract (sorgaab) was used either alone or tank-mixed with 50% of the label dose of iodo+mesosulfuron. Label dose of this herbicide and a weedy check were maintained for comparison. Zero tillage reduced weed density and dry biomass and resulted more grain yield even in weedy control relative to the rest of the tillage practices. Recommended iodo+mesosulfuron dosage and its 50% reduced dose tank-mixed with sorgaab had greater weed suppression in zero tillage in terms of weed density and dry biomass. These treatments also improved wheat leaf area index and crop growth rate. Highest grain yield (4.52 t ha-1 )was obtained with label herbicide dose followed by its 50% reduced dose tank mixed with sorgaab (4.28 t ha-1) under zero tillage system. Highest net benefits (Rs. 163951 ha-1) were associated with the use of label herbicide dose in all tillage practices. Sorgaab application in zero tillage produced higher marginal rate of return (MRR) 37.23, while all other tillage practices had lower MRR due to higher cost involved. Sowing of wheat is recommended in zero tillage with use of tank mixture of sorgaab with 50% of the label herbicide dose to manage weeds.